Believing, Doubting, Deciding, Acting - Clyde Moneyhun (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
I used Peter Elbow's believing and doubting games and cooked up two games of my own, to structure a first-year writing class aimed at teaching students to read and reason critically. The first new game has been hinted at by Elbow himself: the deciding game, in which students used their exercises in believing and doubting to make up their minds about a topic. The second new game, which my students called the living game, asked them to extend their intellectual decisions into the world and take or recommend actions based on them. This was all enacted through a series of assignments for reading journal entries, a term paper, and an elaborate oral presentation. !learned a lot from teaching the course this way, including the enduring power of unreflective skepticism in my students' ingrained thinking patterns.